Hormones and sexual functioning in menopausal transition - (:unkn) unknown (My University, 2007)
Objective: The relative contribution of hormones (androgens and estrogen) to female sexuality and psychosocial status is controversial in menopausal transition. Materials and Methods: We compare the changes of hormonal and psychosocial factors in perimenopausal women with the changes of sexual function. Results: Among DHEAS, FSH, LH, estradiol and free Testesterone (T), free T is the only variable that is significantly associated (P<0.05) with sexual satisfaction. Conclusion: Sexual functioning declines with the menopausal transition. Endogenous hormone levels except androgens do not seem to explain this decline.
Keywords: Hormones; Menopausal transition; Sexuality